2018
DOI: 10.3389/fneur.2018.01060
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Lesion Outcome Prediction Based on MRI Imaging Combined With Clinical Information

Abstract: In developed countries, the second leading cause of death is stroke, which has the ischemic stroke as the most common type. The preferred diagnosis procedure involves the acquisition of multi-modal Magnetic Resonance Imaging. Besides detecting and locating the stroke lesion, Magnetic Resonance Imaging captures blood flow dynamics that guides the physician in evaluating the risks and benefits of the reperfusion procedure. However, the decision process is an intricate task due to the variability of lesion size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 27 publications
(39 reference statements)
1
46
0
Order By: Relevance
“…Some initial studies have shown that machine learning can be used to predict stroke lesions. [9][10][11][12][13] Convolutional neural networks are a subtype of machine learning that does not require humans to define relevant features but instead learns them from data in a training set.…”
Section: Introductionmentioning
confidence: 99%
“…Some initial studies have shown that machine learning can be used to predict stroke lesions. [9][10][11][12][13] Convolutional neural networks are a subtype of machine learning that does not require humans to define relevant features but instead learns them from data in a training set.…”
Section: Introductionmentioning
confidence: 99%
“…Besides clinical and patient data, medical experts rely on multi-modal Computed Tomography (CT) and Magnetic Resonance (MR) imaging for diagnoses and treatment decisions (Baird & Warach, 1998;Chilla, et al, 2015). To both support physicians in their diagnosis and accelerate treatment decision-making, methods for automatic image analysis are increasingly integrated into acute stroke care (Feng, et al, 2018;Pinto, et al, 2018). Deep Convolutional Neural Networks (CNNs) are state-of-the-art to recognize pathological features such as ischemic stroke lesions on brain images (Bernal, et al, 2019;Havaei, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…al. combined CNN features and a SVM classifier to automatically predict genotypes from brain MRIs [3]. An end-to-end learning allows features learning and classifier training to work collaboratively, resulting in a more meaningful and stronger deep representation that leads to state-of-the-art performance on brain tumor segmentation [1,2,[4][5][6][7] and stroke lesion segmentation [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%